2017
DOI: 10.5902/1980509828631
|View full text |Cite
|
Sign up to set email alerts
|

Substâncias Húmicas Em Cambissolo Sob Vegetação Natural E Plantios De Pinus Em Diferentes Idades

Abstract: RESUMODevido à grande área ocupada com reflorestamentos de pinus no sul do Brasil, considera-se necessário avaliar o impacto dessa cultura no estoque de carbono orgânico do solo, especialmente com relação às frações das substâncias húmicas (SH). Nesse contexto, o presente trabalho teve como objetivo avaliar as alterações na quantidade e proporção das substâncias húmicas da matéria orgânica em solo representativo do Planalto Catarinense devido à substituição da vegetação natural por povoamentos de Pinus taeda. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…SOM chemical fractionation showed that most of the TOC was protected in the more stable and recalcitrant fraction (C-HUM), regardless of the system and soil depth (Table 2), corroborating other studies (Freitas et al, 2020;Almeida et al, 2021;Frazão et al, 2021). The C-HUM fraction comprises compounds of higher molecular weight, lower number of carboxylic groups, and higher number of nitrogenous groups, providing higher stability and remaining time in the soil (Pfleger, Cassol, & Mafra, 2017), allowing most TOC to be stored in this fraction. Coser et al (2018) also related this storage to the formation of humus-clay colloidal complexes.…”
Section: Carbon In the Fulvic Acid (C-fa) Humic Acid (C-ha) And Humin...supporting
confidence: 86%
“…SOM chemical fractionation showed that most of the TOC was protected in the more stable and recalcitrant fraction (C-HUM), regardless of the system and soil depth (Table 2), corroborating other studies (Freitas et al, 2020;Almeida et al, 2021;Frazão et al, 2021). The C-HUM fraction comprises compounds of higher molecular weight, lower number of carboxylic groups, and higher number of nitrogenous groups, providing higher stability and remaining time in the soil (Pfleger, Cassol, & Mafra, 2017), allowing most TOC to be stored in this fraction. Coser et al (2018) also related this storage to the formation of humus-clay colloidal complexes.…”
Section: Carbon In the Fulvic Acid (C-fa) Humic Acid (C-ha) And Humin...supporting
confidence: 86%
“…These results can be explained by differences in the soil qualities in the experiments, as these soils present integrated physical, chemical and biological properties (Srivastava et al, 2019). When converting natural areas into pine forests, these properties are modified, increasing the content and stabilization of organic carbon in the soil that is strongly influenced by rotation (Pfleger et al, 2017). This seems to be the most plausible explanation for the different averages for the experiments herein, since the Guatambu area was previously occupied by a Pinus sp.…”
Section: Resultsmentioning
confidence: 81%
“…The HA/FA ratio is used as an indicator of the humification process and represents the level of evolution of SOM (Pfleger et al, 2017). Ratios greater than 1.0 are indicative of greater transformation in SOM.…”
Section: Soil Covermentioning
confidence: 99%